Penguatan Profil Pelajar Pancasila Pada Generasi Alpha Melalui Pendidikan Karakter di Sekolah Dasar - Indrarwansyah, Awianti; Utari, Isma Dini; Ikhbal, Muh (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
This research aims to analyze the strengthening of the Pancasila Student Profile in Generation Alpha through character education in elementary schools. Using the Systematic Literature Review (SLR) method and a meta-synthesis approach, this study integrates findings from 15 scientific articles related to student character development in the context of Merdeka Curriculum. The results show that project-based character education is effective in shaping the dimensions of the Pancasila Learner Profile, such as critical reasoning, creativity, independence, and mutual cooperation. The main challenges include students' low learning motivation and teachers' difficulties in integrating technology in learning. Proposed strategies include the use of technology-based interactive modules and increased collaboration between teachers, students and parents. This research provides strategic guidance for the implementation of character education relevant to Generation Alpha's learning style